A Complete Approach in Implementing Islamic Early Childhood Character Education at the Pandemic Covid 19 Era - Nurhayati, Sri; Parhan, Muhamad (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2024)
The aim of this research is to describe how a unique Islamic early childhood education system, named Tahfiz Anak Usia Dini (TAUD), implemented and contributed substantially to the character education of its students. In total, 6 teachers, 50 parents of 25 students of TAUD SAQU Nurul Islam Al Husna, Indonesia were interviewed, participated in focus group discussions, and 25 students were closely observed. Findings suggest that TAUD Saqu Nurul Islam Al Husna adopts the complete approach of character education which is laid on Islamic principles. The majority of teachers and parents reported that TAUD Saqu Nurul Islam Al Husna educates and develops the character of students by conveying knowledge, providing role models, and supportive environment, then giving chances to practice and form. The paper proposes a model of character education at early childhood education, as well as other Islamic education systems which have similar characteristics on the implementation of character education. Recommendations for future research and practice are also explained.